Preparation of new perovskite ferroelectric compound - Saeed, Harith M.; AlShakarchi, Emad (Edelweiss Applied Science and Technology, 2024)
The main objective of the research is to prepare a new ferroelectric compound with a perovskite phase. This is done by mixing several materials of different phases and with different concentrations to prepare that new intended compound by solid state reaction method; Using the Phase diagram, each of its three angles represents a compound of one of the three ferroelectric compounds Batio3, BiNatio3 and BiLitio3. Then, through the specified area, called morphotropic phase Boundary three points (arbitrary Points) are taken, the point one was (Bi0.48175 Na0.465 Li0.001675 Ba0.0365 Tio3), point two was (Bi0.48675 Na0.475 Li0.01175 Ba0.0265 Tio3) and point three was (Bi0.492 Na0.485 Li0.007 Ba0.016 Tio3) that are projected onto the Phase Diagram coordinates to find out.